EFFORTS TO IMPROVE RELAY RUNNING LEARNING OUTCOMES BY APPLYING RECIPROCAL TEACHING STYLE TO CLASS VIII STUDENTS OF SMP NEGERI 4 TANJUNGBALAI IN THE 2021/2022 ACADEMIC YEAR - Siti Aminah (Indonesia Sport Journal, 2022)
This study aims to improve the learning outcomes of relay running by applying a reciprocal teaching style to class VIII students of SMP Negeri 4 Tanjungbalai in the 2021/2022 academic year. This research is a classroom action research with the stages of implementation including planning, implementing actions, observing, and reflecting. The location of this research was carried out in class VIII of SMP Negeri 4 Tanjungbalai which is located at Jalan IR. H. Juanda Tanjungbalai City. The time of this research was carried out in February 2022. While the subjects of this study were class VIII students of SMP Negeri 4 Tanjungbalai in the odd semester of the 2021/2022 academic year with a total of 32 students. And the object of this research is the Improvement of Relay Running Learning Outcomes by Applying Reciprocal Teaching Style to Class VIII Students of SMP Negeri 4 Tanjungbalai in the 2021/2022 Academic Year. In the initial data (before the cycle) the average score of students was 64.12 where from 32 students there were 10 students who had completed or got scores above the minimum limit. This means that only 31.2% of students achieve classical completeness of the total number of students. For that researchers need to make some improvements in learning. This is realized by the author by using the application of reciprocal teaching styles to improve the learning outcomes of relay running. Then a test was carried out to obtain data on learning outcomes in Cycle I of relay running with the application of reciprocal teaching styles, namely 18 students (56.25%) who had reached the learning mastery level, while 14 students (43.75%) had not yet reached the learning mastery level. With an average value of 74. Then the relay running learning was carried out again with a reciprocal teaching style in cycle II which added a form of exercise to students. From the learning outcomes test conducted in the second cycle, 29 students (90.6%) achieved the mastery level of learning, while 3 students (9.4%) had not yet reached the mastery level in learning, with an average score of 85.34. In this case, it can be seen that there is an increase in the average value of learning outcomes in cycle I and cycle II, which is 11.34. So there is an increase between cycle I and cycle II. Based on the results of the research above, it can be concluded that through the application of reciprocal teaching styles can improve the learning outcomes of relay running in class VIII students of SMP Negeri 4 Tanjungbalai in the 2021/2022 academic year.Keywords: Relay Running, Reciprocal Teaching Style, Classroom Action Research